2011
DOI: 10.1177/1077546311403179
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid input shaping to suppress residual vibration of flexible systems

Abstract: This paper presents a hybrid input shaping method to eliminate residual vibration of multi-mode flexible systems. This method, initially designed for one degree of systems, is modified to apply on linear and nonlinear multi-mode systems. In this method, firstly the flexible system is uncoupled using modal analysis method, and then the parameters of the decoupled system are used to shape the command template signal. A ramp plus ramped cycloid plus ramped versine is proposed as the command template signal to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…is method was selected because S filtered can appear as such a signal source. By using EMD, S filtered is decomposed into two parts, as shown by Figure 6 and (14). It should be noticed that the starting point and nal point of S 2 ′ is di erent with S 1 .…”
Section: Main Principle Of R-istmentioning
confidence: 99%
See 2 more Smart Citations
“…is method was selected because S filtered can appear as such a signal source. By using EMD, S filtered is decomposed into two parts, as shown by Figure 6 and (14). It should be noticed that the starting point and nal point of S 2 ′ is di erent with S 1 .…”
Section: Main Principle Of R-istmentioning
confidence: 99%
“…Another trajectory S 2add , which is similar with S 2 ′ , is added. After the compensating process, (14) becomes (15):…”
Section: Main Principle Of R-istmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence of impulses is obtained using the input shaping described in Section 4.1. to increase the robustness of the signal. The method suggested by Yavuz et al [25] is named as hybrid input shaping. For a specified travelling time and displacement, hybrid-shaping technique is implemented as follows;…”
Section: Hybrid Input Shapermentioning
confidence: 99%
“…Kapucu et al [24] on the other hand, suggested a hybrid input shaping method that includes convolution of a cycloid plus ramp function with two impulse sequences. Yavuz et al [25] proposed a hybrid input shaping method to eliminate residual vibration of multi-mode system by convolving the pre-shaped input of cycloid-plus-ramped versine-ramp function with the sequence of all modes generated by twoimpulse sequences. Conker et al [26] suggested an enhanced control technique for hybrid input shaping method to elimination of residual vibrations in flexible-joint manipulator.…”
Section: Introductionmentioning
confidence: 99%